Labor standards and efficiency estimation of farms in the Kansas Farm Management Association - Holland, Cody (Kansas State University, 2012)
The objectives of this thesis are to examine the labor requirements of Kansas crop and livestock enterprises and farms and the connection between labor efficiency and productivity, and other important farm characteristics including farm size and type. The derived labor requirements are compared to current KFMA labor requirements. Enterprise summary reports and a five year whole-farm panel data set from 1,016 Kansas Farm Management Association (KFMA) farms are used in the analysis. Whole-farm labor requirements are computed with and without an adjustment for managerial and overhead cost. Individual regressions will be estimated to determine the effects that farm size, type, region and profit margin have on labor requirements. The estimation results suggest that many of the current labor requirements still in use are accurate. However, there are enterprises with labor requirements that need updating. When the newly estimated requirements are compared to the previous KFMA requirements, 14 enterprises have lower labor requirements. Irrigated alfalfa showed the greatest decrease in labor required when compared to the previous standard, decreasing from 3.85 hrs/acre to 1.70 hrs/acre. Regression estimation results indicated that whole farm labor standards that were corrected for un-allocated overhead and managerial costs appear to be a more accurate representation of farm labor requirements.
Keywords: KFMA; Labor Standard; Labor efficiency; Labor productivity; Economics, Agricultural (0503)